(3GdYGbHI hGdehJ hGdfTQ hGdMTQ hGdLfI hGdfGQs - (3YHO GdMb Hf YHO GdQMef Hf YHO Gddg GdCROj GdETHjdj, CHh eMeO, GdeYQha H` GHf GdNQGW,J (B581 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CPd HGdehJ QbGH GdLHGHQI CeG HYO aEf GdehJ CeQ cHGQ s
(3BNQgG (B:s
(3aEf JZeOfi Yah hKbJ Hg QHi hGdE aEf WGYI GdfGQ Je GdcJGH HMeO Gddg hMSf Yhfg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B92s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(267 (3b(B) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs